Patient Frustration with Pelvic Organ Prolapse Education Met with Resilient Response. Issue 1 (16th November 2021) - Corley, Elizabeth M.; Terse, Pranaya; Paulosky, Kayla E.; Karsalia, Moli; Nemirovsky, Amy; Malik, Rena D.
Abstract: Introduction: Limited patient understanding due to challenges in physician–patient communication and inadequate patient education materials (PEMs) can result in poor outcomes after pelvic organ prolapse (POP) repair. Our objective was to identify how patients learned about POP and review their perception of available educational tools. Methods: Patients with a history of POP were recruited using ResearchMatch and invited to participate in a virtual semi‐structured interview where they were shown a website, brochure, and video pertaining to POP. Information regarding patient preference for PEMs was obtained. The interviews were transcribed, coded, and qualitative data analysis was performed using grounded theory methodology. Results: Qualitative analysis of interviews of 13 participants averaging 58 years old yielded several preliminary themes including: insufficient information to guide treatment decisions, preference for multimodal, dynamic, and comprehensive materials, and lack of support leading to avoidance of care, misinformation, and self‐advocacy mechanisms. Emerging concepts included: lack of complete information regarding POP treatment resulted in misinformation, stress and desperation, distrust of healthcare providers leading to feelings of isolation, desire of support groups, and loss of follow up, and a desire for well‐organized, detailed, multimodal, and destigmatizing materials as a guide to their disease process, prevention and risk factors, its natural progression, and treatment decisions. Participants developed self‐reliant strategies for making treatment decisions, including the use of online resources, advice from friends, and independent search for more specialized physicians. Conclusions: Women with POP reported a lack of information and support which resulted in the generation of self‐coping mechanisms. This led to significant anxiety surrounding their diagnosis and treatment and poor satisfaction. Developing a reproducible methodology to create evidence‐based PEMs will significantly decrease patient misinformation, apprehension, and use of inaccurate sources of information.